QUALITY EVALUATION OF WELL WATERS IN RURAL AND INDUSTRIAL AREAS, ROMANIA COUNTRY - Maria Alexandra Hoaghia; Melinda Kovacs; Erika Levei; Mirela Miclean; M. Roman; M. Senila; C. Tanaselia; D. Ristoiu (Agricultura, 2015)
The quality of well waters used as drinking water sources from rural and industrial areas, Romania Country was assessed. For quality evaluation, the water quality index was used. Studied well water samples present good and excellent status, according to the water quality index scores. Results show low values for the index, ranging from 15.76 to 37.35, which indicates good quality. Highest values were obtained for the well water samples collected from the rural area. This water quality status was imprinted by high NO3 concentrations and high total hardness, which exceed maximum admissible concentration and drinking water guidelines. The well water samples collected from the industrial area show the highest SO42 concentration and electrical conductivity. All well water samples indicate circumneutral pH, ranging from 7.27 to 7.62 pH units.